KKL-model of MHD CuO-nanofluid flow over a stagnation point stretching sheet with nonlinear thermal radiation and suction/injection - S.A. Mohammadein (Results in Physics, 2018)
In this study, we analyzed numerically the effects of magnetic field and thermal radiation on forced-convection flow of CuO-water nanofluid past a stretching sheet with stagnation point in the presence of suction/injection. Considering the effects of Brownian motion, we applied the Koo–Kleinstreuer–Li (KKL) correlation to simulate the effective thermal conductivity and viscosity of the nanofluid. The equations governing the flow transformed to ordinary differential equations and solved numerically using the fourth-order Runge–Kutta integration scheme featuring a shooting technique. The influence of significant parameters such as the magnetic parameter, radiation parameter, suction/injection parameter and velocity ratio parameter on the velocity and temperature profiles are discussed and presented through graphs and analyzed for (CuO-water). Keywords: Thermal radiation, Suction/injection, MHD flow, Stagnation point, Heat transfer